Effects of Sludge Characteristics on the Critical Flux of an AnMBR for Sludge Treatment. Issue 9 (21st June 2021) - Lutze, Robert; Engelhart, Markus
Abstract: Anaerobic membrane bioreactors for sludge digestion enable extensive degradation of organic matter with reduced reactor volume. The filtration efficiency mainly determines capex and opex. Filtration efficiency (critical flux in this study) for all digested sludges tested with TS > 2.5 % depended in particular on the apparent viscosity at the membrane surface. It did not correlate sufficiently with, among others, total solids concentration and the capillary suction time. The critical flux was improved by increasing the rotational speed (crossflow) and by reducing the viscosity of the digested sludge by adding iron salts. Abstract : This study covers the dependency of the critical flux from sludge characteristics in AnMBR applications for sludge treatment. The critical flux depended in particular on the viscosity at present shear at the membrane surface. Improvements in performance were achieved by increasing the crossflow and by reducing the feed viscosity adding iron salts.